Modeling of development optimization in Balakhani-Sabunchu-Ramana field (V horizon) - NASIBOVA, Gultar; ZEYNALOVA, Sevil (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2026)
Background. This paper presents the principals of application relevance methods for modeling and optimizing the development process, such as Shewhart control charts. This method provides a guide to a detailed development process that addresses various issues that often arise when implementing waterflooding in both offshore and onshore oil and gas fields, in extraction of fluids from reservoir, challenges in well drilling, in oil recovery etc. Using the Shewhart control charts method, it was possible to obtain an adequate answer to the problem (adjustment of the development process) when studying the issues of optimizing the dynamics of oil production from the field. At the same time, this method is useful both for the analysis of all dynamic series and for individual segments (stages). The purpose of constructing control charts is to identify the points at which the process leaves a steady state in order to subsequently determine the causes of the deviations that have arisen and eliminate them. The purpose of constructing Shewhart control charts is to determine the boundaries of the system variability of the process and to predict the behavior of the process in the near future based on past process data. Methods. Development curves have been constructed using geological and field data. This graph allows determining the optimal development regime, recalculating oil and gas reserves, and fully reflecting the effective extraction of hydrocarbons from the field. Results. Analyzing the relationship among development curves, pressure recovery, oil and gas production growth rates for various development periods adjustment is possible. Conclusions. As a result of the research conducted using the Shewhart control charts dynamic model, it was possible to control and regulate the development processes of the V horizon of the Balakhany-Sabunchu-Ramana field, which is an exploitation object, as well as to determine the optimality levels of these processes and the effectiveness of using appropriate methods to increase the oil recovery factor. This method proved effective in increasing production, can effectively enhance the production performance during the optimization process. This is crucial for implementing refined management of individual horizons, determining the exit beyond of development regulation limits.
Keywords: development curves; Shewhart control charts; deviations; regulation; optimal development; exploitation object